Failure of intravascular ultrasound to identify the site of recurrent focal coronary spasm during stenting. Issue 6 (14th May 2004) - Azeem, T; Adlam, D; Gershlick, A
Abstract : Focal coronary spasm is often associated with an area of mural plaque disease. This report describes a patient with recurrent severe coronary spasm unresponsive to medical treatment. Coronary arteriography and intravascular ultrasound identified a candidate area of minor coronary atheromatous disease but ergonovine provocation testing showed the spastic coronary segment to be distal to and distinct from this area. Coronary stenting of the site identified by ergonovine provocation testing was effective in relieving provoked and spontaneous spasm.